2012
DOI: 10.2319/012012-49.1
|View full text |Cite
|
Sign up to set email alerts
|

Is missing maxillary lateral incisor in complete cleft lip and palate a product of genetics or local environment?

Abstract: Cleft-side MxI2 agenesis in CLP subjects appears to be largely a genetically controlled anomaly associated with cleft development, rather than a collateral environmental consequence of the adjacent cleft defect, since increased hypodontia involving multiple missing teeth observed remote from a cleft clearly has a significant genetic basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
4
16
0
1
Order By: Relevance
“…These results confirm findings of previous research investigations, which suggest that tooth agenesis encompassing multiple missing teeth has been clearly identified under genetic control of multifactorial inheritance [2830]. Several of these critical genetic controls assume a mutual part in the development of orofacial clefts [31].…”
Section: Discussionsupporting
confidence: 90%
“…These results confirm findings of previous research investigations, which suggest that tooth agenesis encompassing multiple missing teeth has been clearly identified under genetic control of multifactorial inheritance [2830]. Several of these critical genetic controls assume a mutual part in the development of orofacial clefts [31].…”
Section: Discussionsupporting
confidence: 90%
“…A possible explanation for this association is that genes related to tooth agenesis also may influence the early phase of the palatal closuring process. These findings reinforce the hypothesis of a common genetic background for palate cleft and tooth agenesis, in agreement with literature reports for unilateral cleft lip and palate (15,25).…”
Section: Dental Anomaly Groupsupporting
confidence: 93%
“…The occurrence of cleft palate and the development of tooth germs have a close embryological relationship between chronological and anatomical terms, and several studies have reported the manifestation of dental anomalies associated with several forms of cleft lip, cleft palate, or both (13,23). The pattern of associated dental anomalies has been studied in patients without clefts (2,(7)(8)(9)(10)(11)24), and the studies about these dental anomalies in patients with oral clefts are few (14,15,25).…”
Section: Introductionmentioning
confidence: 99%
“…Cleft patients have considerably more dental anomalies than non-cleft patients [ 1 ]. Certain key genetic disturbances have been implicated in both dental anomalies and clefting, suggesting a shared genetic etiology in some cases [ 2 , 3 ]. Among many dental anomalies reported in CLP patients, small tooth size is frequently reported [ 3 - 6 ].…”
Section: Introductionmentioning
confidence: 99%